(untitled) (Boletin Médico de Postgrado, 2017)
Neurogenic bladder is characterized by inability to store, empty urine or both, which originates in the nervous system, excluding psychogenic. In pediatric patients is due to congenital abnormalities: spina bifida and other neural tube defects being the most frequent myelomeningocele, degenerative neuromuscular disorders, cerebral palsy, VACTERE (vertebral malformations, Annals, Cardiovascular, Tracheal, Esophageal, Renal, Tips) syndrome and acquired lesions: brain trauma, spinal cord, pelvic nerves. Among the therapeutic options for this disease, from conservative management, drug therapy to surgical procedures, when the previous ones have failed. This study is a cross descriptive investigation, whose sample is not probabilistic intentional based on criteria of inclusion and exclusion, applying as surgical management of Neurogenic Bladder surgical technique Ileovesicostomia by principle Yang - Monti in pediatric patients from the Urology Decentralized Service of the University Pediatric Hospital "Dr. Agustín Zubillaga. "A data collection sheet was implemented to get the information, which was processed using SPSS version 15, the data were analyzed using descriptive statistics techniques. In the period studied the surgical management of neurogenic bladder was performed in 3 patients, mainly boys aged between 6 and 9 years, surgical time interval between 7-12 hours with an average of 9.85 hours, hospital stay 15 days average, and three-month follow-up without evidence of complications. According to the results it is determined that the technique Ileovesicostomia Yang - Monti is applicable and provides practical results that allow the patient to obtain biopsychosocial being.